Implementation of Web-Based Case Midwifery Notes Documentation System (CMNotes) for Intra Natal Care - Cut Mutiah; Abdurrahman Abdurrahman; Rayana Iswani; Isnaini Putri; Muhammad Nazar (Postgraduate, University of Mataram, 2023)
Case Midwifery Notes (CMNotes) is a digital-based documentation system designed to develop learning methods and interactive consultations between students and lecturers. CMNotes facilitates digital and comprehensive recording of patient data starting from assessment, diagnosis, plan of care, implementation to evaluation by applying Varney's management principles and SOAP documenta-tion. This study aims to design produce a documentation system for midwifery care emphasized on the Intranatal care. The app was developed using php and html followed by hosting via wordpress. The data was collected using pssuq instrument (usability assessment), need analysis instrument and student responses questionnaire. 63 students from Midwifery student of Health Polytechnic Aceh were involved in the implementation of the system. The implementation results show that overall score of the system usability measured using PSSUQ is 2.87 indicating that the CMNotes system provides convenience and satisfaction for students in making documentation of childbirth care. Due to comments of users regarding the practi-cality of system, it is necessary to develop an Android-based CMNotes application to be able to fill in patient data more easily and effectively without the need of internet access.